The influence of Federal Regulations and community health indicators on community benefit spending by private nonprofit hospital in some States of the US: A retrospective longitudinal correlational study - Wael ELRAYES; David PALM; Fernando WILSON; Hongmei WANG; Jane MEZA; Robin HIGH; Valerie PACINO (Journal of Health and Social Sciences)
Introduction: In the United States, private nonprofit hospitals are exempt from federal, state, and local taxes in exchange for providing community benefits. Federal legislation in 2007 and 2010 established a standard re- porting format that allowed researchers to examine community benefit spending patterns by private nonprofit hospitals, though this continues to be an understudied subject. The aim of this study was to assess whether the recent federal regulations and community health indicators influenced community benefit spending by private nonprofit hospitals in seven US states. Methods: A retrospective longitudinal study was used to estimate the relationship between county-level com- munity health indicators in one year and levels of spending on community health improvement initiatives in the consecutive year for 223 urban and rural counties in seven US states. A generalized linear mixed model with lagged community health indicators and included multiple covariates was used. Results: Only two of the fourteen community health indicators included in the analytical model were signifi- cantly associated with spending on community health improvement initiatives. The ratio of population to pri- mary care physicians was positively associated with spending (P < 0.0001), while adult smoking was negatively associated with spending on these activities (P = 0.003). Discussion: Major variations exist in spending on community health improvement initiatives between counties in the same state and across different states. States with the highest health needs spent the least, while those with lowest health needs spent the most. The remarkable fluctuation in spending over the three years of the study could not be explained by a matching variability in the community health needs. Additional research should examine what factors influence the spending decisions by private nonprofit hospitals on community health improvement activities.